2002
DOI: 10.1007/s00223-001-1121-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Deficiency Increases Mineral Content and Mineral Crystallinity in Mouse Bone

Abstract: Fourier transform infrared microspectroscopy (FTIRM) and infrared imaging (FTIRI) were used to characterize the mineral in bones of two different lines of Opn-deficient (Opn-/-) mice and their background-matched wild-type controls (Opn+/+). Sections of tibia and femur from 12-week-old and 16-week-old mice were evaluated with a spatial resolution between 10 microm (FTIRM) and 7 microm (FTIRI). FTIRI was used to examine 400 microm x 400 microm areas in cortical bone and trabecular bone and FTIRM examined selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
219
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(243 citation statements)
references
References 0 publications
16
219
0
8
Order By: Relevance
“…(34) Thus, both the full-length protein and its peptides appear to be important in the inhibition of mineralization. Corroborating the present work, other studies have shown increased levels of OPN in disease models of osteomalacia, suggesting an important role for OPN in regulating normal mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…(34) Thus, both the full-length protein and its peptides appear to be important in the inhibition of mineralization. Corroborating the present work, other studies have shown increased levels of OPN in disease models of osteomalacia, suggesting an important role for OPN in regulating normal mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin is a secreted glycoprotein which limits hydroxyapatite formation and deposition [100,101]. Pyrophosphate can induce osteopontin in osteoblasts via the MAPK signalling pathway [28,102] and both Enpp1 -/-and ank/ank mice display reduced osteopontin expression in osteoblasts and decreased serum levels of the protein [28,44,45].…”
Section: Pyrophosphate: the Mechanism Of Actionmentioning
confidence: 99%
“…Firstly, pyrophosphate has to be injected as it is ineffective orally because of hydrolytic destruction within the gut; BPs are effective by mouth despite being poorly absorbed. Secondly, pyrophosphate does not inhibit bone resorption, whereas this is the key pharmacological action of BPs when used to treat clinical disorders characterised by excessive resorption [100]. BPs are very effective drugs with more than 40 years of clinical use, and have proven to be remarkably safe, with an excellent benefit to risk ratio [109].…”
Section: Pyrophosphate and Bisphosphonatesmentioning
confidence: 99%
“…In vitro studies by several groups have established that OPN is an inhibitor of calcification [17,18]. Bones from OPN-knockout mice have a greater mineral content and contain larger hydroxyapatite crystals than wild type animals [19]. It is probable that osteocytes elaborate OPN to inhibit the growth of hydroxyapatite in the wall of their lacuna and in the canaliculi to avoid burying due to secondary mineralization.…”
Section: Discussionmentioning
confidence: 99%